Central mechanisms of airway sensation and cough hypersensitivity. (December 2017) - Driessen, Alexandria K.; McGovern, Alice E.; Narula, Monica; Yang, Seung-Kwon; Keller, Jennifer A.; Farrell, Michael J.; Mazzone, Stuart B.
Abstract: The airway sensory nervous system is composed of two anatomically distinct processing pathways that allow for the production of respiratory reflexes and voluntary evoked respiratory behaviours in response to sensing an airway irritation. Disordered sensory processing is a hallmark feature of many pulmonary disorders and results in the development of cough hypersensitivity syndrome, characterised by chronic cough and a persistent urge-to-cough in affected individuals. However, the mechanism underpinning how the airway sensory circuits become disordered, especially at the level of the central nervous system, is not well understood. In this mini-review we present well-defined mechanisms that lead to the development of chronic pain as a framework to explore the evidence that cough disorders may manifest due to neuroplasticity and sensitisation of important components of the airway sensory circuitry in the brain. We highlight recent discoveries of how airway sensory processing occurs in the brain in health and disease and additionally suggest areas where gaps exist in our current knowledge on the topic, with the goal of providing a better understanding of how airway circuits become dysfunctional in disease. This may in turn help identify novel therapeutic targets for restoring normal airway sensory processing and alleviating excessive cough.